HYDROUS COMPONENT IN THE GARNET OF ECLOGITE FROM THE WEST TIANSHAN - Su W.; Gao J.; Xiong X.M.; Klemd R. (My University, 2006)
The main elements and hydroxyl within garnets of eclogites from the west Tianshan were examined using electron microprobe at Fourier infrared spectroscopy. As a result, the garnets show zoning composition: that is spessartite in the core and pyrope in the rim. Our data show that the hydroxyl component decrease gradually from rim (about 367-658ppm) to core (about 89-239ppm), where contains relative high Mn concentrations. It imply that large amount of aqueous fluids were released by the dehydration reactions during the transition from blueschist to eclogite. The hydrous components participate in the high-pressure metamorphism and formation of eclogitic minerals. The core of garnet crystallized at the rich Mn and water concentration conditions. The part of water at core of garnet is preserved as OH in the garnet with high-pressure metamorphism.
Keywords: DISTRIBUTION; ECLOGITE; GARNET; WEST TIANSHAN; WATER